Dark Passages of the Bible - Ramage, Matthew J. (Book collections on Project MUSE., 2013)
Following the lead of Pope Benedict XVI, in Dark Passages of the Bible Matthew Ramage weds the historical-critical approach with a theological reading of Scripture based in the patristic-medieval tradition. Whereas these two approaches are often viewed as mutually exclusive or even contradictory, Ramage insists that the two are mutually enriching and necessary for doing justice to the Bible's most challenging texts.